The Tarjīḥ Method of Imām Nawāwi in Resolving Differences of Opinion in the Shāfi'ī School of Thought - Manaf, Abd.; ., Jamaluddin; ., Zarkasyi; Nirwana, A.N., Andri; Elbanna, Mariam (al-'adalah, 2024)
This study aims to analyze the tarjīḥ method used by Imām Nawāwi to reconcile the different opinions among Syāfi’ī Scholars, as presented in the book of Minḥāj al-Ṭālibīn wa ʿUmdat al-Muftīn. This research is a qualitative, descriptive literature study with a normative juridical approach. This study found that the book Minḥāj al-Ṭālibīn wa ʿUmdat al-Muftīn consists of several key elements in the form of (1) Ikhtiṣar (summary) in which Imām Nawāwi simplifies the explanation for each topic to facilitate understanding and memorization. (2) Classification of Terms: Here, he puts forward specific terms, such as al-Azhār, Qawl al-Jadīd, and Qawl Qādim, to differentiate between Imām Syāfi'ī's own opinion and the opinion of his followers. In this way, it can be identified which opinions come from the pure thought of Imam Syāfi'ī and which come from the thoughts of his ulama followers. (3) Imām Nawāwi In carrying out Tarjīḥ, he uses several methods at once, namely the Bayānī method (textual analysis), the Taʽlīlī method (cause-based analysis), and the Istislāhī method (analysis based on public interest). This study concludes that the book Minḥāj al-Ṭālibīn wa ʿUmdat al-Muftīn not only functions as a guide to understanding Syāfi'ī fiqh but can also be a model for developing Tarjīḥ methods that are systematic and in line with the dynamics of the development of Islamic legal science.